Penentuan Kandungan Antioksidan Total pada Infusa Selada Hijau (Lactuca sativa L.) Hidroponik dan Konvensional secara Spektrofotometri dengan Modified Phenantroline Method (MPM) - Yefrida Yefrida; Refilda Refilda; Nofi Hamidah; Widuri Rosman (Universitas Andalas, 2022)
Green lettuce is a vegetable that is widely consumed in Indonesia. These vegetables come from conventional and hydroponic farming. This study aims to compare the antioxidant content of these two types of vegetables. This vegetable is extracted by the infundation method. The extract obtained was determined for its antioxidant content by the MPM method. This method was validated by using parameter LoD, LoQ, linearity, precision and accuracy. The results showed that this method was valid for determining the total antioxidant content in conventional and hydroponic green lettuce samples. The total antioxidant content in conventional and hydroponic green lettuce samples was 2.68 Â± 0.65 mg aa/g FW and 1.67 Â± 0.40 mg AA/g FW, respectively. T test stated that the antioxidant content of the two samples was significantly different.